2020
DOI: 10.3390/ijms21165643
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Is Required for The Anti-Epileptic Effects of AMPA Receptor Antagonists in Chronic Epileptic Rats

Abstract: α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) is one of the ligand-gated ion channels for glutamate, which is an important player in the generation and spread of seizures. The efficacy of AMPAR functionality is regulated by the trafficking, synaptic targeting, and phosphorylation. Paradoxically, AMPAR expression and its phosphorylation level are decreased in the epileptic hippocampus. Therefore, the roles of AMPAR in seizure onset and neuronal hyperexcitability in ictogenesis remain to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 56 publications
4
31
1
Order By: Relevance
“…Considering the role of CREB in GRIA surface expression [ 47 ], it is plausible that PTEN-mediated CREB dephosphorylation may be relevant to the downregulation of GRIA1 induced by AMPAR antagonists. Consistent with our previous study [ 35 ], total GRIA1 protein level in the epileptic hippocampus was 0.71 ± 0.02-fold of control level ( t (12) = 9.3, p < 0.001 vs. control animals, Student t -test; Figure 7 A,B, Figure S6 ), which was further reduced to 0.54 ± 0.03 and 0.58 ± 0.03-fold of control level in responders by perampanel and GYKI 52466, respectively ( F (2,17) = 12.7, p < 0.001 vs. vehicle, one-way ANOVA; Figure 7 A,B, Figure S6 ). GRIA1 surface expression in the epileptic hippocampus was 0.87 ± 0.02-fold of control level ( t (12) = 4.9, p < 0.001 vs. control animals, Student t -test; Figure 7 A,C, Figure S6 ), which was also decreased to 0.54 ± 0.04 and 0.62 ± 0.04-fold of control level in responders by perampanel and GYKI 52466, respectively ( F (2,17) = 25.7, p < 0.001 vs. vehicle, one-way ANOVA; Figure 7 A,C, Figure S6 ).…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Considering the role of CREB in GRIA surface expression [ 47 ], it is plausible that PTEN-mediated CREB dephosphorylation may be relevant to the downregulation of GRIA1 induced by AMPAR antagonists. Consistent with our previous study [ 35 ], total GRIA1 protein level in the epileptic hippocampus was 0.71 ± 0.02-fold of control level ( t (12) = 9.3, p < 0.001 vs. control animals, Student t -test; Figure 7 A,B, Figure S6 ), which was further reduced to 0.54 ± 0.03 and 0.58 ± 0.03-fold of control level in responders by perampanel and GYKI 52466, respectively ( F (2,17) = 12.7, p < 0.001 vs. vehicle, one-way ANOVA; Figure 7 A,B, Figure S6 ). GRIA1 surface expression in the epileptic hippocampus was 0.87 ± 0.02-fold of control level ( t (12) = 4.9, p < 0.001 vs. control animals, Student t -test; Figure 7 A,C, Figure S6 ), which was also decreased to 0.54 ± 0.04 and 0.62 ± 0.04-fold of control level in responders by perampanel and GYKI 52466, respectively ( F (2,17) = 25.7, p < 0.001 vs. vehicle, one-way ANOVA; Figure 7 A,C, Figure S6 ).…”
Section: Resultssupporting
confidence: 94%
“…GluN2B Y1472 site is dephosphorylated by PTEN [ 37 ]. Recently, we have reported that PTEN expression level in the epileptic hippocampus is lower than that in the control, and the anti-epileptic effects of AMPAR antagonists require the upregulations of its expression in responders [ 35 ]. However, we have not explored the effects of AMPAR antagonists on PTEN phosphoryaltion level in both responders and non-responders.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations